2009
DOI: 10.1080/13546780903040666
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants of dual goal facilitation in a rule discovery task

Abstract: Wason's standard 2-4-6 task requires discovery of a single rule and leads to around 20% solutions, whereas the dual goal (DG) version requires discovery of two rules and elevates solutions to over 60%. We report an experiment that aimed to discriminate between competing accounts of DG facilitation by manipulating the degree of complementarity between the to-be-discovered rules. Results indicated that perfect rule complementarity is not essential for task success, thereby undermining a key tenet of the goal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
1
24
2
Order By: Relevance
“…It is not clear, however, why DG instructions should necessarily lead to a greatly enhanced breadth of triple testing. It is also not the case that such breadth is consistently observed with DG instructions (Gale & Ball, 2009) Previous research by Gale and Ball (e.g., 2003;2009) has suggested an alternative mechanism by which DG instructions might facilitate task performance. This mechanism is based on the "contrast class cues" that are afforded by MED feedback, with these cues enabling participants to clarify the scope of the DAX rule as relating to "ascending" sequences.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…It is not clear, however, why DG instructions should necessarily lead to a greatly enhanced breadth of triple testing. It is also not the case that such breadth is consistently observed with DG instructions (Gale & Ball, 2009) Previous research by Gale and Ball (e.g., 2003;2009) has suggested an alternative mechanism by which DG instructions might facilitate task performance. This mechanism is based on the "contrast class cues" that are afforded by MED feedback, with these cues enabling participants to clarify the scope of the DAX rule as relating to "ascending" sequences.…”
mentioning
confidence: 76%
“…In support of their theory, Wharton et al reported a study in which DG instructions failed to elicit facilitated performance when the complementary nature of the rules was left implicit. However, a recent experiment by Gale and Ball (2009) directly manipulated the relationship between the experimenter's two rules such that triples could be DAX, MED or "neither DAX nor MED" (i.e., the DAX and MED rules were no longer logically complementary), yet the level of facilitated performance was equivalent to that observed with the usual DG instructions. Gale and Ball's (2009) findings therefore confirm that rule complementarity is not the causal factor underpinning the DG facilitation effect (see also Vallée-Tourangeau et al, 1995, for a study similar to that of Gale & Ball, 2009, which likewise produced evidence opposing the goal complementarity hypothesis).…”
mentioning
confidence: 99%
See 3 more Smart Citations